2015
DOI: 10.1002/smll.201500823
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Optical Signature of Plasmonically Coupled Nanocrystal Quantum Dots

Abstract: Small clusters of two to three silica-coated nanocrystals coupled to plasmonic gap-bar antennas can exhibit photon antibunching, a characteristic of single quantum emitters. Through a detailed analysis of their photoluminescence emissions characteristics, it is shown that the observed photon antibunching is the evidence of coupled quantum dot formation resulting from the plasmonic enhancement of dipole-dipole interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
(103 reference statements)
1
26
1
Order By: Relevance
“…1 and Supplementary Table 4). Importantly, by employing time-gated second-order autocorrelation function ( g (2) ) analysis, we are able to confirm the single-nanostructure nature of the tetrapods being investigated (separating effects of possible tetrapod clustering from that of multiexciton emission on g (2) values; if g (2) values remain >0.5 after a time-gating procedure is applied, then a cluster rather than a single nanostructure is being interrogated—see Supplementary Note 2)4142. The single-tetrapod PL spectra show that with increasing pump fluence longer-arm tetrapods (TP3 and TP4) afford robust dual CdSe-red and CdS-green PL, while shorter-arm tetrapods (TP1 and TP2) do not.…”
Section: Resultsmentioning
confidence: 95%
“…1 and Supplementary Table 4). Importantly, by employing time-gated second-order autocorrelation function ( g (2) ) analysis, we are able to confirm the single-nanostructure nature of the tetrapods being investigated (separating effects of possible tetrapod clustering from that of multiexciton emission on g (2) values; if g (2) values remain >0.5 after a time-gating procedure is applied, then a cluster rather than a single nanostructure is being interrogated—see Supplementary Note 2)4142. The single-tetrapod PL spectra show that with increasing pump fluence longer-arm tetrapods (TP3 and TP4) afford robust dual CdSe-red and CdS-green PL, while shorter-arm tetrapods (TP1 and TP2) do not.…”
Section: Resultsmentioning
confidence: 95%
“…We verified these assignments and obtained accurate evaluations of / and C / S by performing two sophisticated analyses. In the first, called time-gated g (2) analysis, the g (2) curve was analyzed by applying a time gate to the PL decay curve [29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…1(b). TPCE has been studied not only on widely-used CdSe/ZnS and CdSe/CdS core-shell NCs [13][14][15][16][17][18][19][20][21][22][23][24] but also in various other systems, such as NCs coupled with metallic objects [27][28][29][30][31][32] and NCs with emerging materials [33][34][35]. Investigations of TPCE reveal much more details about the photo-absorption and recombination processes in single NCs [24], when compared to investigations of excitons.…”
Section: Introductionmentioning
confidence: 99%
“…126 In contrast, Wang et al recently demonstrated that small clusters of two to three SiO 2 -coated g-QDs coupled to a plasmonic (gold) gap-bar antenna can exhibit complete photon antibunching-a characteristic of single quantum emitters, despite multiple optically active g-QDs being present ( Figure 5b ). 128 Through a detailed analysis of their emission characteristics, they further showed that the observed photon antibunching resulted from plasmonics-enhanced dipoledipole interactions (i.e., metal-induced formation of a coupled QD-QD emissive state). In this case, the presence of the SiO 2 shell yielded a QD-QD separation distance of at least 30 nm, rendering alternative interpretations of the data, such as conventional dipole-dipole interaction, not physically possible.…”
Section: Plasmon-assisted Coupling Between Individual Emittersmentioning
confidence: 98%